2022
DOI: 10.3126/jafu.v5i1.48475
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of Ageratum houstonianum Mill intoxicated goats

Abstract: Ageratum houstonianum Mill (A. houstonianum) is a widespread, highly invasive, and drought-resistant annual semi-shrub easily found in the pasture fields. It is called Gandhey Jhar locally. This study was conducted at the livestock farm of Rampur Campus, Rampur, Chitwan, Nepal, to determine the clinical progression and clinical parameters in A. houstonianum intoxicated goats to diagnose its toxicosis in small ruminants. Full blossomed A. houstonianum was fed ad libitum to six goats until the death of the anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…According to the local people, A. houstonianum was confined to the agro-ecosystems for a long time, but from the last 8-10 years, the species has invaded forest ecosystems even under tree canopies. Previous studies have reported that A. houstonianum is poisonous to livestock (Shrestha et al 2019, Bhatta et al 2022. The community people of the current study site have also reported the livestock poisoning of this species.…”
Section: Terminalia-shorea-trewia Community (C-5)mentioning
confidence: 49%
“…According to the local people, A. houstonianum was confined to the agro-ecosystems for a long time, but from the last 8-10 years, the species has invaded forest ecosystems even under tree canopies. Previous studies have reported that A. houstonianum is poisonous to livestock (Shrestha et al 2019, Bhatta et al 2022. The community people of the current study site have also reported the livestock poisoning of this species.…”
Section: Terminalia-shorea-trewia Community (C-5)mentioning
confidence: 49%
“…Ageratum houstonianum distribute on grasslands and agro-ecosystems and forest with under high tension line (Panedy et al 2021;Sapkota et al 2023). The IAP and its toxic capacity the animal and livestock are in threat (Bhatta et al 2022;Pertin et al 2018;Sapkota et al 2023;Shrestha et al 2019a). The wild animal is in vulnerable condition in the forest ecosystem (Chaudhary et al 2020;Lu et al 2014).…”
Section: Impact Of the Invasive Alien Plant Species On Terrestrial Ec...mentioning
confidence: 99%